The Way to the Leading Positions in World Tourism: Case Study of Kazakhstan - KULAKHMETOVA, Gulbaram A.; HNATKOVYCH, Oksana D.; RUSNAK, Alla V.; SHCHERBAKOVA, Nadiia A. (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018, 2019)
The work is a problem of competitiveness of Kazakhstan among the countries of the world in the development of the tourism industry. The work shows that in recent years the country has risen to a higher position in the world rankings. The authors demonstrate that for the advanced improvement of the position of Kazakhstan among other countries in the development of tourism, it is necessary to take into account certain criteria for evaluation. It is also necessary to pay attention to how other countries are developing and what they are doing in order to occupy a leading position in the rating. The work determines which areas of the economy need to be developed to attract tourists. The work says that the President of Kazakhstan of his new program for the development of the country has already begun to implement a strategy for accelerated industrial and innovative development of the tourism industry. The emphasis is on the revival of the Silk Road for the growth of trade between Europe and Asia. The novelty of the research is that the article mentions the results of the world scale latest statistics, on the basis of which the analysis of the state development of the tourism industry in Kazakhstan was carried out. The authors came to the conclusion that improving the indicators should follow a certain plan, not forgetting to pay attention to the experience of other countries.